Development of Accuracy Evaluation Method for Open Loop Educational CNC Milling Machine - Winarno, Agustinus; Lasiyah, Sus; Tulung Prayoga, Benidiktus; Aris Hendaryanto, Ignatius; Sukidjo, Fransiskus Xaverius (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
The open-loop educational computer numerical control (CNC) milling machine requires accuracy verification in order to ensure its accuracy and functionality. In this paper, the new verification method is proposed based on the length measurement using the fringe counting of He-Ne laser interferometry. The ideal translation length is defined by the number of electric pulses generated by the micro-stepping driver, while the actual length is measured using He-Ne laser interferometry. In the experimental process, the data of the fringe pattern of the He-Ne laser and the number of electric pulses which drive the stepper motors were simultaneously acquired using an oscilloscope. Hence, the data has been analyzed to obtain the ideal and actual lengths by using an in-house program developed in Python. By comparing the actual translation and ideal length, the accuracy of the educational CNC milling machine has been evaluated to be 50 Âµm for the length up to 200 mm.